Solvophobicity and amphiphilic self-assembly in neoteric and nanostructured solvents. (February 2020) - Warr, Gregory G.; Atkin, Rob
Abstract: The emergence of ionic liquids and deep eutectics as neoteric solvents that support surfactant self-assembly creates a vast new playing field for creating new forms of soft matter with distinctive properties. Solvophobic self-assembly in ionic liquids and deep eutectics has unique and novel features arising from strong interactions between constituents, high ionic strengths, and the molecular structures of the components, which can induce amphiphilic nanostructure in these nonaqueous solvents. This nanostructure is often reminiscent of microemulsions and sponge phases. Here we review recent new understanding of solvent nanostructure and its effect on self-assembly of surfactants and lipids. Graphical abstract: Image 1